A longitudinal cohort study of the impact of first-and both-eye cataract surgery on falls and other injuries in Vietnam - To, K.; Meuleners, Lynn; Bulsara, M.; Fraser, Michelle; Duong, D.; Do, D.V.; Huynh, V.N.; Phi, T.; Tran, H.; Nguyen, N. (Dove Medical Press, 2014)
Aim: Little information exists on the impact of cataract surgery on falls and other injuries in Vietnam. The aim of this study was to determine the impact of first and both eye cataract surgery on the number of falls and other injuries among bilateral cataract patients in Ho Chi Minh City, Vietnam. Materials and methods: A longitudinal cohort study was conducted involving 413 bilateral cataract patients aged 50+ years. Participants were assessed at three time points: 1 week before, 1–3 months after, and 1 year after first-eye cataract surgery. Visual measures (visual acuity, contrast sensitivity and stereopsis) were taken, and self-reported falls and injury data were collected. A multilevel longitudinal Poisson regression model was used to investigate change in the number of falls after surgery. Results: The risk of falls decreased by 78% (incidence-rate ratio [IRR] 0.22, 95% confidence interval [CI] 0.06–0.77; P=0.018) in the year after cataract surgery for participants who had first-eye surgery only and 83% (IRR 0.17, 95% CI 0.04–0.69; P=0.012) for participants who had the second eye operated on compared to before surgery. The risk of falls was three times higher for females than males (IRR 3.13, 95% CI 1.53–6.40; P=0.002). Improved binocular contrast sensitivity was also associated with a decrease in falls (IRR 0.40, 95% CI 0.17–0.97; P=0.042). The prevalence of other injuries also decreased after cataract surgery. Conclusion: Cataract surgery reduced the number of falls and other injuries in Vietnam. Contrast sensitivity may be important for ophthalmologists to consider when prioritizing patients for surgery and assessing their fall risk.